A Study of The Attitudes and Motivations of Learning of Junior High School Students on The Technological Process in Islamic Studies - Alessandra Oldani; Forcella Chiara; Mozzi Monica (Journal Neosantara Hybrid Learning, 2023)
The influence of technological processes is something that can no longer be separated from human life today, including the field of education. Students’ responses and acceptances of the technological process determine the extent to which this technology can be used in the learning process. The purpose of this study is to find out how the influence of attitudes and motivations for learning from junior high school students on the technological process in Islamic studies. This research uses quantitative methods with a survey model. The tool used in this survey model is a questionnaire on a google form. The results found in this study are that learning attitudes and motivations in students largely determine developments in the technological process in Islamic studies. From this research, it can be concluded that the existence of a technological process in Islamic studies will shape the character of students for the better and increase student learning motivation. The limitation of this study is that researchers only conduct research on the attitudes and learning motivations of junior high school students regarding technological processes in Islamic studies. Researchers hope that subsequent researchers can conduct similar studies at the level of education and other subjects.